Herméneutique, pragmatisme et critique des institutions - Michel, Johann (Social Science Information, 2014)
This article examines the ‘question of meaning’ in institutions by distinguishing several levels of both meaning and analysis. The institution presents itself (semantic level) as an objectified configuration of meaning whose historicity (socio-genetic level) we should be able to reconstruct. Although it has stabilized over time, the objectified meaning is subject to modification by situated lived interactions (pragmatic level). If institutions cannot exist without a naturalized and pre-reflexive relation to rules and roles, we nevertheless need to distinguish intermediate levels of reflexivity without these necessarily having to challenge the established order. Because institutions, which are always contingent, are ‘fragile’, those who occupy dominant positions carry ‘additional meaning’, on top of the immanent meaning of the rules and roles. This additional meaning, as a legitimation device, is assimilated to a meta-pragmatic level. The present article, then, seeks to ‘graft’ a plurality of hermeneutic theories, stemming from textual science, onto these levels of analysis, in order to increase the intelligibility of the institutional phenomenon.